Principles of Grouping the Images of Saints in Byzantine Monumental Painting before and after Iconoclasm - Zakharova, Anna V. (Actual Problems of Theory and History of Art, 2014)
Images of saints are important elements of Eastern Christian church decoration. From the 11th c. on they were arranged in a hierarchical system embodying the unity of all types of holiness. The saints were usually represented in groups according to their status (profession) and commemoration day and placed in certain order in the church interior. The author tries to find out, how and when this tradition formed? A survey of surviving ensembles of mosaics and wall-paintings from the 5th to the 10th c. shows that during this period the selection and grouping of saints was based on different principles. Before the Iconoclasm only some major categories, like apostles, prophets and martyrs were singled out. The echelon of saintly bishops started to single out in the art of the 7th–9th cc. Only in the ensembles of the 10th – beginning of the 11th c. there appear a more diversified and structured system of representing different categories of saints, which would later become classical for the art of Byzantium and other Orthodox countries.